Zooplankton community structure in Pengkalan Chepa river basin - Fadzli, Siti Zulfarina (2015)
A study was conducted on zooplankton composition and physico-chemical parameters at five different stations within Pengkalan Chepa River Basin, Kelantan. The study was carried out starting from May 2010 until February 2011 covering both dry (May 2010 till August 2010) and rainy seasons (November 2010 till February 2011) using Wisconsin net of 20 cm in diameter and mesh size of 63 micron meter (μm). The study was aimed to document the zooplankton community and evaluate the water quality of the river using this zooplankton compositions and structure. Approximately 157 species of zooplankton identified, consisting of 32 families from three major groups. The order of zooplankton groups that are dominating the rivers, in descending order were: rotifers (99 species) > copepods (38 species) > cladocerans (22 species). Rotifers was the most dominant group contributing to about 62% of all zooplankton densities, followed by copepods (24%) and cladocerans (14%). Brachionus urceolaris which accounts for 53.51% of all zooplankton population was the most dominant zooplankton species. Marine copepods were also observed due the intrusion of seawater from the nearby estuary into the nearest sampling station. The study found that Pengkalan Chepa River Basin was inhabited by a few high profile pollution-tolerant species such as Brachionus sp., Anuraeopsis fissa, Moina micrura, and Rotaria rotatoria. The existence of these types of plankton species alongside the variations of physico-chemical conditions during the study indicated moderate to poor river health that was contaminated.